Too hot to handle? A social semiotic analysis of touching in "Bend it like Beckham". Issue 1 (2nd January 2016) - Garratt, Dean; Piper, Heather
Abstract: This article examines the cinematic portrayal of touching and its politics in sports coaching, exploring how social interactions between coach and athlete are symbolically represented. The analysis focuses primarily on a well-known British-produced film, Bend it like Beckham (2002), in which scenes exhibit different forms of touching. The construction of intimate coach–athlete relationships captured through a series of filmed encounters is analysed through a social semiotic frame. This requires judgements about the authority, "reality-status" and possibility of meaning arising from such representational practices. Attention is drawn to different moments of intimacy and/or sexual tension between the lead coach and central female characters, both on and off the pitch. Through a series of detailed interpretations, we show how the complexities involved in assigning intentionality in cinematic contexts serves both to assert and displace meaning. This further problematises moral aspects of relations between coaches and athletes in tactile encounters, and especially so within the context of risk-averse safeguarding policies in sports coaching, a context characterised by increased prescription, proscription and disciplinary intervention during the years since the film was released.